Multi-Objective Optimization for Dehydration of Jaggery in Vacuum Dryer by Grey Relational Analysis - M.V. Pisal, Prof.Dr.S.S.Gawade (International Journal of Advanced Science and Technology, 2020)
Jaggery is a traditional sweetener and more nutritious than sugar. Therefore,jaggery has been demanded a lot in the global market. Shelf life and user-friendly appearance are the two biggest challenges. If jaggery is available in powdered form, due to value addition, more earnings are possible to sugarcane producers-farmers. This article focuses on an approach based on the Taguchi method with grey relational analysis for optimizing the vacuum drying parameters duringthe drying of Jaggery. To produce jaggery in granular form, it is required to dehydrate it up to 2%.The main objective of this study is to obtaina higher material rate (yield), lower drying time, and good quality of Jaggery powder.Drying temperature, Vacuum pressure, and quality of dehydrated jaggery are the three process parameters. Since the process has multiple performance characteristics, the grey relational analysis is used. The grey relational grade normalizes the contradicting performance indices. From eighteen experiments based on the orthogonal array of L18, the best possible combination of parameters was found. Compared with Taguchi’s method, the proposed method is more technically sound. The experimental results confirm that the proposed method effectively improves the drying performance of Jaggery.